USE OF VALPROIC ACID IN WOMEN WITH EPILEPSY DURING PREGNANCY - A. V. Yakunina; I. E. Poverennova; V. A. Kalinin; S. A. Nenasheva (Эпилепсия и пароксизмальные состояния, 2017)
Objective: to evaluate the use of valproic acid in treatment of epilepsy during pregnancy.Material and Methods. The maternal and obstetric outcomes of 601 pregnancies in women with epilepsy in the Samara region were reviewed. The incidence rates of fetal major congenital malformations (MCM) in women with epilepsy were analyzed; the data were obtained from the Samara regional MCM registry and from EURAP – the European epilepsy and pregnancy registry (report dated November, 2016). The development of intelligence (IQ) in 23 children born to women with epilepsy and 10 children of healthy women was assessed.Results. Among the 601 pregnant women with epilepsy, 219 (36.4±2.0%) received no antiepileptic drugs (AED), 290 patients (48.3±2.0%) received AED monotherapy, and 92 patients (15.3±1.5%) – AED polytherapy. Fetal MCM were diagnosed in 19 of 601 women with epilepsy (3.2±0.7%); of those five MCM cases were attributed to monogenic and chromosomal abnormalities. The reported incidence of MCM in the population of the Samara region is 2.7%. However, within the present study we found deviations from the standard protocol of MCM registration; therefore, we assume that the real MCM incidence rate in the regional population is higher. The rate of fetal MCM in women exposed to AED monotherapy was 3.1±1.0%, with polytherapy – 4.3±2.1%, and in the untreated women – 0.5±0.5%. The rate of MCM was relatively higher after exposure to valproic acid monotherapy (4.7±1.7%) than that for carbamazepine monotherapy (3.1±2.2%); these figures were still considered to be within the limits of low genetic risk. Notably, the present rates of MCM incidence for the Samara region were lower than those reported in EURAP. Among the children born to the women with epilepsy, the general, verbal and non-verbal IQ averaged at 128.8; 116.5 и 133.3 points (respectively), which did not significantly differ from the IQ values in children born to the women without epilepsy. Likewise, no significant differences were found between the IQs of children exposed in their fetal period to valproate or carbamazepine and those who were not exposed to antiepileptic drugs.Conclusion. If good seizure control is reached with valproic acid, this drug can be used during pregnancy at the lowest effective dose.